Penerapan Rest API untuk Sistem Informasi Film Secara Daring - Yanti, Sari Noorlima; Rihyanti, Erni (Jurnal Informatika Universitas Pamulang, 2021)
The number of movie website sites makes users confused which website to visit in order to get information from a movie that is being searched for. Moreover, the information provided is still minimal, making it ineffective in maximizing the use of time. With current technological developments, applications have been successfully created based on websites. Not only can it be enjoyed by PC / Laptop users, users who make smartphones as their main device can also feel comfortable using this application. The application design process is carried out using the JavaScript and CSS programming languages as a form of layout. Later it will be associated with an API that provides data for all types of films called the TMDb API. On this website there are rules and regulations that must be done. Likewise, you are required to register as a member to get an API key, so that access can be used. The method in designing applications uses SDLC which aims to focus on each stage that is carried out.